Marketing Strategy For Micro Small To Medium Enterprises at 777 Sweet Fruit Shops in Gowa District - Najib, Marhawati; Jannah, Miftahul; Syam, Agus (PT. Maju Malaqbi Makkarana, 2024)
The growth of MSMEs is increasingly widespread, especially the 777 fruit sweet shop business which markets various kinds of fruit, both local and imported. In the current era, MSME players should be able to utilize digital media to market their products so that consumers become more familiar with the products produced by these MSMEs. This research aims to determine the marketing strategy carried out by the 777 fruit sweet shop business to increase sales. This research is descriptive research using a qualitative approach. The informant was determined deliberately, namely the business owner of Sweet Fruit Shop 777. The data collection procedures used in the research included observation, interviews, and documentation. The data obtained was analyzed using SWOT analysis. Based on the research results, show that the strategy implemented by the 777 fruit sweet shop business in Gowa Regency, South Sulawesi Province is in quadrant one, namely Aggressive (growth-oriented strategy), which is a very profitable situation with implementation through Marketing Strategy. The coordinates of point x are the coordinates of the IFAS strategy with a coordinate point of 2.83, while the coordinates of point y are the coordinates of the EFAS strategy with a coordinate point of 2.07. The strategy that needs to be improved in fruit marketing is to make maximum use of digital marketing to reach a wider market.